Directions for Increasing Green Energy Capacity of Uzbekistan: Petunjuk untuk Meningkatkan Kapasitas Energi Hijau Uzbekistan - Bakhtiyorovich, Toshboyev Bekzod (Academia Open, 2024)
General background: The global transition to renewable energy is essential for mitigating climate change and ensuring energy security, and Uzbekistan, with its abundant natural resources, holds significant potential. Specific background: Despite progress, Uzbekistan still relies heavily on fossil fuels, and challenges remain in integrating renewable energy into the national grid. Knowledge gap: Previous studies have focused on the technical and economic benefits of green energy, yet there is limited research on the interplay between market reforms and renewable energy adoption in developing nations like Uzbekistan. Aims: This research aims to assess the current renewable energy policies and propose strategies to enhance Uzbekistan’s capacity, particularly in solar and wind energy. Results: The findings reveal that while Uzbekistan has made strides, substantial reforms in market liberalization and increased investment are necessary to meet its 2030 green energy targets. Novelty: This study offers new insights by integrating a market-based approach to energy reforms with the need for targeted subsidies and international investment, filling a critical gap in the literature on green energy transitions in developing economies. Implications: The results suggest that further policy adjustments, enhanced international cooperation, and financial incentives are vital for accelerating Uzbekistan’s green energy transition, providing a model for similar economies. Highlights: Uzbekistan needs substantial market reforms to increase green energy capacity. Solar and wind energy are key to meeting the 2030 renewable energy goals. Targeted subsidies and international investment are essential for sustainable energy development. Keywords: Solar Energy, Wind Energy, Energy Subsidies, Energy Investments, Market Liberalization